2015
DOI: 10.1530/eje-15-0617
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oxidative stress and autoimmunity in Hashimoto's thyroiditis

Abstract: Objective: We have aimed to study the relation between Hashimoto's thyroiditis (HT) and thyroid autoantibodies and oxidative stress parameters in euthyroid, subclinical and overt hypothyroid stages. Design and methods: A total of 124 patients were included in the study; 93 of whom were newly diagnosed with HT (31 patients in each of the euthyroid, subclinical hypothyroid and overt hypothyroid subgroups), aged over 18 and had not received any prior treatment and 31 of whom were healthy volunteers. Results: Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 35 publications
9
82
0
1
Order By: Relevance
“…For instance, Nanda et al (6) reported higher oxidative stress levels in anti-TPO (+) patients with hypothyroid compared with anti-TPO (−) patients with hypothyroid. Three different studies also had reported higher oxidative stress levels in HT compared with healthy controls, supporting our data (4,9,10,16).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For instance, Nanda et al (6) reported higher oxidative stress levels in anti-TPO (+) patients with hypothyroid compared with anti-TPO (−) patients with hypothyroid. Three different studies also had reported higher oxidative stress levels in HT compared with healthy controls, supporting our data (4,9,10,16).…”
Section: Discussionsupporting
confidence: 91%
“…Data from previous studies suggest that oxidative stress level may be increased due to chronic inflammation (3), deficient thyroid hormone levels (4), excessive autoimmune response, or excessive iodine intake (5) in HT. Reports of higher oxidative stress markers in hypothyroid patients with antithyroid peroxidase (anti-TPO) positivity compared with those without (anti-TPO (-)) (6) and increasing oxidative stress levels by the progression of HT from euthyroid to overt hypothyroid stage (7,8,9) also supported previous data. In the light of these studies, it may be suggested that oxidative stress levels may have been increased in hypothyroid stage of HT, where thyroid hormone deficiency is at maximum levels (9).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The results of studies conducted on oxidative stress in hypothyroid patients are conflicting. Ateş et al (32) investigated total antioxidant status in euthyroid, subclinical and clinic patients secondary to Hashimoto's thyroiditis, and observed it to be lowered in clinical hypothyroid patients when compared to healthy controls and other groups. However, oxidative stress index and total oxidant status were significantly higher in clinic hy-pothyroid patients than in the other groups and higher in euthyroid and subclinical patients than the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism, as well as CV diseases like chronic HF, are associated with oxidative stress, in which altered levels of NO, asymmetric dimethyl arginine (ADMA) and glutathione peroxidase enzymes (selenoproteins that remove hydrogen peroxide and harmful lipid hydroperoxides) exacerbate endothelial dysfunction [12,13,14]. Recently, a study demonstrated that oxidative stress is higher in overt hypothyroid patients than in euthyroid or subclinical hypothyroid patients, and the total antioxidant status is lower in overt hypothyroid subjects compared to the other groups [15]. …”
Section: Introductionmentioning
confidence: 99%